2008
DOI: 10.1063/1.2991164
|View full text |Cite
|
Sign up to set email alerts
|

The role of anisotropy in the response of the titanium alloy Ti–6Al–4V to shock loading

Abstract: Manganin stress gauges in lateral orientation have been used to monitor the shock response of Ti–6Al–4V when loaded either parallel to or radial to the long axis of the original bar stock studied in this investigation. Materials characterization has shown that the c-axis of the hexagonal unit cell is preferentially orientated radially to the axis of the bar. Shear strengths measured along the long axis of the bar were found to be in agreement with previous data in the literature, while strength in the radial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Experimental observations on rolled [1,3,4] and extruded [5] engineering alloys show that crystallographic and morphological textures can induce strongly anisotropic damage growth and fracture behavior. Texture has also been found to result in anisotropic spallation of low-symmetry metals under shock loading [6,7]. Most available theories of dilatational viscoplasticity, however, make use of the simplifying assumption that the matrix material is homogeneous and isotropic, and are therefore unable to capture texture effects.…”
Section: Introductionmentioning
confidence: 97%
“…Experimental observations on rolled [1,3,4] and extruded [5] engineering alloys show that crystallographic and morphological textures can induce strongly anisotropic damage growth and fracture behavior. Texture has also been found to result in anisotropic spallation of low-symmetry metals under shock loading [6,7]. Most available theories of dilatational viscoplasticity, however, make use of the simplifying assumption that the matrix material is homogeneous and isotropic, and are therefore unable to capture texture effects.…”
Section: Introductionmentioning
confidence: 97%
“…Millett et al [67] studied the effects of crystallographic texture on the shock response of Ti6Al-4V by loading material with a strong texture in the longitudinal and radial directions. No variation in the equation of state was found between the two conditions, but it was shown that the shear strength (again, by using embedded manganin gauges in sectioned targets) was lower in the radial direction which was attributed to the orientation of the HCP unit cell relative to the loading direction.…”
Section: (A) Shock Response Of Titaniummentioning
confidence: 99%
“…The load-displacement responses of the high-purity Ti tested in shear differ substantially consistent with the large differences in the yield stresses of high-purity Ti [71] previously documented in the literature between in-plane and through-thickness orientations. The high-purity Ti displays a significant difference in its shear response between the TT and IP directions consistent with the strong basal texture of the material [72], making the TT direction the higher flow stress direction. Shear loading in both the TT and IP directions for the high-purity Ti displayed significant strain hardening, more than a factor of 2 increase in load carrying capacity after yield, with the hardening rate higher in the TT sample, as indicated in Fig.…”
Section: Mechanical Response Of the Materialsmentioning
confidence: 69%